COVID-19 in Saudi Arabia: An Overview - Salam, Asharaf Abdul; Al-Khraif, Rshood M.; Elsegaey, Ibrahim (Frontiers in Public Health, 2022)
Background: Saudi Arabia, a prominent Arabian country, has 35.3 million persons living in 2.2 million square kilometers, undergone serious threats, recently, due to the COVID-19 pandemic. With the built in infrastructure and disciplined life, the country could address this pandemic. Aims: This analysis of COVID-19 cases in Saudi Arabia, attempts to assess the situation, explore its global percentage share, percentage of population affected, and local distribution from the beginning of infection till recently, tracing historical developments and changes. Data and methods: This analysis made use of data released by the Ministry of Health on a daily basis for a number of parameters. They are compiled on excel sheet on a daily basis: the dataset has undergone rigorous analysis along the trends and patterns; proportion to the world statistics and geographic distribution. Results: COVID-19 spread rapidly in the country with periodic variations, spreading rapidly across the country during June-August, 2020. But, recoveries accelerated in the period and thus bridging the gap of increasing infections. In comparison with the world statistics, the country proportions are lesser: similar is the percentage of population affected. Apparently, all the 13 administrative areas are affected with varying intensity. Conclusion: COVID-19 transmission since March, 2020 considered to be wide spread creating excess burden on public health system, delineated into stages (early infection, rapid spread, declining, stabilizing, and second wave). Control measures are set, stage wise, without impinging upon normal life but to ensure that the proportion to global affected persons is lesser than the population share; credit goes to the Ministry of Health. Area wise spread depend largely on population density and development infrastructure dimensions. Ultimately, the disciplined life in compliance with law and order situation paved way for effective program implementation and epidemic control.